X-ray fluorescence and digital imaging: inspiring students with chemistry and creative technology - da Cunha, Mariana Trassi; Bruschi, Isaac Machado; Pereira-Filho, Edenir Rodrigues; Pereira, Fabiola Manhas Verbi (Eclética Química, 2026)
This study explores innovative ways to enhance chemistry education by leveraging smartphone applications and advanced techniques like digital imaging and X-Ray Fluorescence (XRF) spectroscopy. Students analyze coins of varying colors to link visible differences to their chemical compositions. Images are captured, analyzed, and converted into ten-color scale matrices, enabling students to explore color variations beyond the naked eye's perception. XRF spectroscopy, a non-destructive and rapid method, identifies elemental composition, ensuring safe and practical analysis. The activity emphasizes critical skills such as data organization, modern analysis methods, and elemental identification, which are essential in today’s digital age. Designed for senior students, it fosters curiosity about chemistry by demonstrating its everyday relevance. Students learn how Digital Imaging (DI) and chemometric techniques reveal chemical distinctions, with XRF showcasing how specific elements drive color diversity. This hands-on, creative approach highlights the role of technology in education, inspiring deeper engagement and appreciation for chemistry.